Variations in Cascadia Low‐Frequency Earthquake Behavior With Downdip Distance. (27th February 2019) - Sweet, Justin R.; Creager, Kenneth C.; Houston, Heidi; Chestler, Shelley R.
Abstract: We identify and characterize four different low‐frequency earthquake (LFE) families (LFEs 1–4, ordered updip to downdip) that span the width of the transition zone in the Cascadia Subduction Zone beneath western Washington State. We find that LFE swarm duration, recurrence interval, and event size decrease systematically with increasing depth. LFE moments are observed to follow an exponential distribution rather than a power law distribution, allowing us to determine a characteristic event size for each family. Absolute locations of these LFE families place them very near the inferred Juan de Fuca‐North America plate interface. Relative relocation of individual LFEs within each family reveal elongation parallel to the plate convergence direction and narrow depth distributions with dips corresponding to plate interface models. We interpret the behavior of our LFE families as indicative of slow slip at those locations on the plate interface. The tidal response of LFE activity at LFEs 1, 2, and 3 during a large episodic tremor and slip (ETS) event follows a previously observed evolution, in which tidal response during the initial 1 to 2 days of slip at an LFE patch is much weaker than that during the next few days of slip. The brief bursts of activity at LFE4, although little affected by large episodic tremor and slip events, respond strongly to tidal stresses. Our observed along‐dip contrasts in recurrence behavior and tidal response provide evidence for stress transfer and increased frictional strength with position updip through the tremor zone. Key Points: Low‐frequency earthquake swarm duration, recurrence interval, and event size decrease systematically with increasing depth Absolute locations of these LFE families place them very near the inferred Juan de Fuca‐North America plate interface Observed LFE behavior provides evidence for stress transfer and increased frictional strength with position updip through the transition zone